Ectodermal dysplasias - Ana L. João; Sofia Antunes-Duarte; Ana Cordeiro; Maria J. Paiva-Lopes (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Ectodermal dysplasias are a heterogeneous group of rare inherited disorders. Molecular findings and clarification of cell signaling processes and ectodermal-mesenchyme interaction enabled the development of a clinical-functional model, which in turn helps to explain clinical signs, with variability in severity, associated non-ectodermal abnormalities and overlap seen in many patients. We herein review the current state of knowledge regarding this distinct entity and illustrate with an elucidative case report. The need for early multidisciplinary intervention is highlighted, and further studies will focus on genetically-target therapeutic approaches.